2019
DOI: 10.1038/s41598-019-53091-8
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Extraction of Important Surgical Phases in Cataract Surgery Videos

Abstract: The present study aimed to conduct a real-time automatic analysis of two important surgical phases, which are continuous curvilinear capsulorrhexis (CCC), nuclear extraction, and three other surgical phases of cataract surgery using artificial intelligence technology. A total of 303 cases of cataract surgery registered in the clinical database of the Ophthalmology Department of Tsukazaki Hospital were used as a dataset. Surgical videos were downsampled to a resolution of 299 × 168 at 1 FPS to image each frame.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…In recent years, the accessibility of big data and the rise of DL potentially enable machines to understand clinical data, particularly surgical videos (23). At present, videobased surgical AI researches show relatively high accuracy in instruments, anatomical structures, and surgical phase recognition in other surgical fields like cataract surgery, gynecological surgery, and laparoscopic surgery (27,(54)(55)(56)(57)(58) (Table 2), showing the potency of AI in the videos analysis of thoracic surgery. The thoracic procedures videos recorded routinely have accumulated as a large and informative data source.…”
Section: Ai-assisted Display Based On Surgical Videomentioning
confidence: 99%
“…In recent years, the accessibility of big data and the rise of DL potentially enable machines to understand clinical data, particularly surgical videos (23). At present, videobased surgical AI researches show relatively high accuracy in instruments, anatomical structures, and surgical phase recognition in other surgical fields like cataract surgery, gynecological surgery, and laparoscopic surgery (27,(54)(55)(56)(57)(58) (Table 2), showing the potency of AI in the videos analysis of thoracic surgery. The thoracic procedures videos recorded routinely have accumulated as a large and informative data source.…”
Section: Ai-assisted Display Based On Surgical Videomentioning
confidence: 99%
“…We found that a CNN alone could predict the core steps of cataract surgery well. Morita et al 8 used Inception V3 to detect continuous curvilinear capsulorrhexis and nuclear extraction in real-time and achieved greater than 90% sensitivity. Our performance was higher in phacoemulsificationand other surgical steps, although performance was lower in capsulorrhexis.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Deep learning has also been successfully applied to cataract surgery analysis. 8 10 However, most studies used videos from a single institute and did not incorporate advanced surgical steps, thus limiting their generalizability.…”
Section: Introductionmentioning
confidence: 99%
“…extraction of two important phases (i.e., the curvilinear capsulorhexis and nuclear extraction phase) was obtained with the aim of preventing complications by evaluating the surgical techniques of inexperienced surgeons too. 50 Yu and coworkers designed five deep learning algorithms to classify a given video segment (belonging to a phase of cataract surgery), previously pre-segmented manually.…”
Section: Scheduling and Perioperative Managementmentioning
confidence: 99%